The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1088/0022-3727/36/4/302
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric properties of residual water in amorphous lyophilized mixtures of sugar and drug

Abstract: Dielectric relaxation spectroscopy was used to investigate the properties of residual water in lyophilized formulations of a proprietary tri-phosphate drug containing a sugar (trehalose, lactose or sucrose) or dextran. The dielectric properties of each formulation were determined in the frequency range (0.1 Hz-0.1 MHz) and temperature range (30˚C-T g ). The temperature dependence of the relaxation times for all samples showed Arrhenuis behaviour, from which the activation energy was derived. Proton hopping thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 21 publications
2
37
0
Order By: Relevance
“…Relaxation times are extremely long in the glassy state but a dramatic decrease in relaxation times occurs above the T g (Williams et al, 1955;Angell et al, 1982;Moynihan, 1993;Perez, 1994;Roos, 1995;Slade and Levine, 1995;Angell, 2002;El Moznine et al, 2003). In our previous study, we found a strong link between the glass transition, a-relaxations and flow characteristics of milk solids (Silalai and Roos, 2010a).…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…Relaxation times are extremely long in the glassy state but a dramatic decrease in relaxation times occurs above the T g (Williams et al, 1955;Angell et al, 1982;Moynihan, 1993;Perez, 1994;Roos, 1995;Slade and Levine, 1995;Angell, 2002;El Moznine et al, 2003). In our previous study, we found a strong link between the glass transition, a-relaxations and flow characteristics of milk solids (Silalai and Roos, 2010a).…”
Section: Introductionmentioning
confidence: 77%
“…The temperature dependence of the a-relaxation time (s a ) was modeled using the Vogel-Tamman-Fulcher (VTF) relationship of Eq. (1) (Chan et al, 1986;Angell et al, 1982;El Moznine et al, 2003;Angell, 2008).…”
Section: Dielectric Analysis (Dea)mentioning
confidence: 99%
“…Interestingly, the temperature of secondary relaxations was found to increase when sucrose was also present in the starch-water matrix indicating the importance of specific interactions in determining the effect on local motions. Moznine et al 80 studied the effect of the interaction of residual water with lyophilized sugars. They observed that the faster noncooperative dielectric relaxations, resulting from a protonic charge transfer process in presence of water, determined the degradation rates of the sugars.…”
Section: Effect Of Water On Secondary Relaxations In Glassy Pharmaceumentioning
confidence: 99%
“…The temperature dependence of the a-relaxation time (s a ) was modeled using the Vogel-Tamman-Fulcher (VTF) relationship of Eq. (1) (Angell et al, 1982;Chan et al, 1986;El Moznine et al, 2003;Angell, 2008).…”
Section: Dynamic-mechanical Analysis (Dma)mentioning
confidence: 99%